1992
DOI: 10.1083/jcb.119.3.549
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of two huge protein components of the brush border cytoskeleton: evidence for a cellular isoform of titin.

Abstract: Abstract. Two extremely high molecular weight proteins were found to be components of the intestinal epithelial cell brush border cytoskeleton. The largest brush border protein, designated T-protein, migrated on SDS gels as a doublet of polypeptides with molecular weights similar to muscle titin T I and T II. The other large brush border protein, designated N-protein, was found to have a polypeptide molecular weight similar to muscle nebulin. In Western analysis, a polyclonal antibody raised against brush bord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 31 publications
0
29
0
Order By: Relevance
“…More recently, evidence for expression of bona fide titin isoforms encoded by the titin gene in smooth muscle has been presented [Labeit et al, 2006]. Previously, our lab has identified a titin-like protein (cellular titin, c-titin) in nonmuscle cells, first in the terminal web domain of the intestinal cell brush border cytoskeleton and then in human blood platelets [Eilertsen and Keller, III, 1992;Keller, III et al, 2000]. Characterization of c-titin isolated from brush borders and platelets revealed that it interacts with a-actinin and arranges nonmuscle myosin II bipolar filaments in a side-by-side and end-to-end ordered array similar to that of myosin II organization in the stress fibers of nonmuscle cells [Eilertsen and Keller, III, 1992;Eilertsen et al, 1994].…”
Section: Introductionmentioning
confidence: 94%
“…More recently, evidence for expression of bona fide titin isoforms encoded by the titin gene in smooth muscle has been presented [Labeit et al, 2006]. Previously, our lab has identified a titin-like protein (cellular titin, c-titin) in nonmuscle cells, first in the terminal web domain of the intestinal cell brush border cytoskeleton and then in human blood platelets [Eilertsen and Keller, III, 1992;Keller, III et al, 2000]. Characterization of c-titin isolated from brush borders and platelets revealed that it interacts with a-actinin and arranges nonmuscle myosin II bipolar filaments in a side-by-side and end-to-end ordered array similar to that of myosin II organization in the stress fibers of nonmuscle cells [Eilertsen and Keller, III, 1992;Eilertsen et al, 1994].…”
Section: Introductionmentioning
confidence: 94%
“…One non-muscle site of titin expression has been reported in the terminal web region of the brush border array of microvilli of intestinal epithelial cells, where it is thought to mediate the association of myosin II and alpha-actinin with the cytoskeleton [Eilertsen and Keller, 1992]. Titin's intracellular interactions are thought to organize and stabilize actin-myosin II associated cytoskeletal structures [Eilertsen et al, 1994].…”
Section: Introductionmentioning
confidence: 99%
“…The powder was extracted using 1ϫ SDS-sample buffer. The SDS extract was fractionated on highly porous 4 -20% gradient SDS-polyacrylamide, as described previously (29). The gel was electroblotted onto nitrocellulose using semidry blot transfer system (Bio-Rad Laboratories) and stained using Ponceau S. The blots were blocked in 5.0% nonfat dry milk for 1-2 h at room temperature.…”
Section: Methodsmentioning
confidence: 99%